2014
DOI: 10.4028/www.scientific.net/amr.996.769
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tempering Conditions on Shot-Peened Tool Steel Components In-Depth Residual Stress Profiles

Abstract: Abstract. Tool steel (X155CrVMo121KU in the following UK15) samples were analyzed to determine the in-depth residual stress profile and to study modifications in the microstructure, induced by a shot-peening treatment. The influence of different tempering temperatures was studied. Residual stress and dislocation density profiles were measured using standard laboratory X-ray diffraction (XRD) residual stress analysis with progressive chemical layer removal. Dislocation density profiles where obtained using a Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…No increase in hardness was detected as a result of the shot‐peening treatment, possibly owning to the high dislocation density from the quenching and low‐temperature tempering at 170°C. Cecchin et al 22 reported that for highly annealed or unquenched materials, shot‐peening resulted in a dislocation pile‐up and subsequent hardness increase towards the surface, whereas materials tempered at 150°C or 300°C featured a decrease in dislocation density and reduction in hardness as a result of the rebounding of the elastically deformed core and a secondary yielding of the surface layer. Measurement of the full width at half maximum diffraction peaks (FWHM), performed alongside the residual stress measurements, support this interpretation as the obtained FWHM measurements at the surface were generally lower than those beyond 50 μm, indicating either a grain coarsening or dislocation annihilation.…”
Section: Surface Integrity Of the Fatigue Specimenmentioning
confidence: 99%
“…No increase in hardness was detected as a result of the shot‐peening treatment, possibly owning to the high dislocation density from the quenching and low‐temperature tempering at 170°C. Cecchin et al 22 reported that for highly annealed or unquenched materials, shot‐peening resulted in a dislocation pile‐up and subsequent hardness increase towards the surface, whereas materials tempered at 150°C or 300°C featured a decrease in dislocation density and reduction in hardness as a result of the rebounding of the elastically deformed core and a secondary yielding of the surface layer. Measurement of the full width at half maximum diffraction peaks (FWHM), performed alongside the residual stress measurements, support this interpretation as the obtained FWHM measurements at the surface were generally lower than those beyond 50 μm, indicating either a grain coarsening or dislocation annihilation.…”
Section: Surface Integrity Of the Fatigue Specimenmentioning
confidence: 99%